2023
DOI: 10.1186/s12864-022-09103-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing for detecting reciprocal translocation carrier status in preimplantation genetic testing

Abstract: Background Balanced reciprocal translocation (BRT) is one of the most common chromosomal abnormalities that causes infertility, recurrent miscarriage, and birth defects. Preimplantation genetic testing (PGT) is widely used to select euploid embryos for BRT carriers to increase the chance of a healthy live birth. Several strategies can be used to distinguish reciprocal translocation carrier embryos from those with a normal karyotype; however, these techniques are time-consuming and difficult to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…To verify the feasibility of T2T‐CHM13 for balanced translocation, we performed a retrospective analysis using patient 2 as the subject 11 . We had already identified the precise breakpoints of 26 208 295 (13q11) and 33 942 281 (17q11.2) using GRCh37.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the feasibility of T2T‐CHM13 for balanced translocation, we performed a retrospective analysis using patient 2 as the subject 11 . We had already identified the precise breakpoints of 26 208 295 (13q11) and 33 942 281 (17q11.2) using GRCh37.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the feasibility of T2T‐CHM13 for balanced translocation, we performed a retrospective analysis using patient 2 as the subject. 11 We had already identified the precise breakpoints of 26 208 295 (13q11) and 33 942 281 (17q11.2) using GRCh37. However, TGS revealed that the actual location of the breakpoint was some distance from the centromere, which was not entirely in line with the karyotype.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate the ability to detect structural rearrangements and distinguish normal from balanced embryos through both a direct approach, leveraging paired-end sequencing information from the embryo samples, and an indirect approach, which involves analyzing flanking haplotypes. Even though various strategies exist to differentiate normal from balanced embryos, including MaReCs 42 , a method based on shallow sequencing 43 , and a method based on Nanopore sequencing technology 44 , they cannot be integrated with other workflows for other PGT purposes as each workflow requires different technologies. Finally, we show the comparability and reproducibility of heteroplasmy levels between traditional day-3 blastomere biopsy with PCR-RFLP and our WGS-PGT method.…”
Section: Discussionmentioning
confidence: 99%
“…TGS has been applied successfully for PGT. Applications have included testing for aneuploidies and structural rearrangement (Tan et al, 2023; Xia et al, 2023). This includes the detection of balanced reciprocal translocations, and identification of breakpoints to within 1 bp (Xia et al, 2023).…”
Section: Diversity and Expansion Of Pgt Genetic Analysis Methods And ...mentioning
confidence: 99%
“…Applications have included testing for aneuploidies and structural rearrangement (Tan et al, 2023; Xia et al, 2023). This includes the detection of balanced reciprocal translocations, and identification of breakpoints to within 1 bp (Xia et al, 2023). In one study, TGS could be performed with fewer reads, and concordance between NGS and TGS was nearly 99% for aneuploidies of 10 Mb or greater, with somewhat better performance of TGS for defects between 5 and 10 Mb, but diminished efficiency for both platforms for detecting defects of <10 Mb, and NGS appeared to perform better for lower quality samples (Tan et al, 2023).…”
Section: Diversity and Expansion Of Pgt Genetic Analysis Methods And ...mentioning
confidence: 99%